KETERTARIKAN KONSUMEN PADA BRAND AMBASSADOR DAN CITRA MEREK PADA KEPUTUSAN PEMBELIAN - Rozalia Rozalia; Handayani Rinuastuti; Rusminah Hs (Distribusi - Journal of Management and Business, 2020)
This study aims to determine the effect of brand ambassadors on brand image and the decision to purchase Nike brand shoes in the city of Mataram. This type of research includes associative research because this study aims to determine the influence or also the relationship between two or more variables. The variables in this study are brand ambassador, brand image, and purchasing decision. The data collection method used is the survey sample method. The population in this study was the people of Mataram, aged >18 years who had bought Nike brand sports shoes at least once, and decided to buy Nike shoes themselves. The sampling technique was purposive sampling, with a sample size of 100. Distribution of questionnaires directly to the location where the study was conducted. The data analysis tool used is Multivariate Regression Analysis using the Partial Least Square (PLS) method and assisted with smartPLS 3.0 data processing tools. The results showed that (1) brand ambassadors had a significant effect on brand image. (2) brand ambassadors have a significant effect on purchasing decisions. (3) brand image has a significant effect on purchasing decisions.